MICROPHYTOPLANKTON DYNAMICS IN CURUPERÉ ESTUARY AT THE AMAZONIAN MANGROVE ECOSYSTEM - Fernanda Nogueira REIS; Lucinice Ferreira BELÚCIO; Fábio Campos PAMPLONA; Luciana Thaila Lopes REIS; Giselle Damasceno VEIGA; Nuno Filipe Alves Correia MELO (Boletim do Instituto de Pesca)
The aim of this study was to evaluate microphytoplankton dynamics and environmental parameters in the estuary of the Curuperé River, located in an Amazonian mangrove ecosystem. Ten sampling sites, where occupied to obtain surface water samples for qualitative and quantitative microphytoplankton analyses, chlorophyll-a, temperature, turbidity, salinity, and pH. Samplings were conducted in four months: in February, May, August and November/2015; the first two months corresponding to rainy season and the last two to dry season. Significant spatiotemporal differences were observed, for diversity, equitability and specific dominance of the microphytoplankton community. In total, 212 taxa were identified and this community was dominated by Bacillariophyta (149 taxa), followed by Myzozoa (29 taxa). The abundance varied from 7,700 ind L-1, (May, sampling site 1) to 343,800 ind L-1, in August (sampling site 4). The diatom Cymatosira belgica was the dominant species, followed by Dimeregramma minor (major peaks of 180,600 ind L-1 and 120,400 ind L-1, respectively) in August at point 4. Phytoplankton biomass indicates an eutrophic estuary as Chlorophyll-a varied from 13.01 to 112.88 mg m-3, probably due to marine shrimp farm effluents. It was possible to identify species strongly indicative of the environment, through analysis of indicator species (IndVal), and their relations with the main environmental conditions (pH, salinity and rainfall), determined by canonical redundancy analysis (RDA).